Adolescent women and non-custodial measures: Narratives of an ethnographic experience - Cecilia Montes-Maldonado; Universidad de la República y Universidad Autónoma de Barcelona; Laura López-Gallego; Universidad de la República; Raquel Galeotti-Galmes; Universidad de la República (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2018)
Adolescent women are historically invisible in juvenile penal systems since there is a hegemonic model of adolescent infraction focused in male and poor adolescents. This article analyzes the particularities of the treatment of adolescent women in the execution of non-custodial measures in the Uruguayan Juvenile Penal System. The methodology is qualitative with an ethnographic approach following the techniques of observation and ethnographic accompaniment of 4 adolescent women, analysis of files and recordings in a field diary. The results narrate the practices of social and criminal control aimed at adolescent women, in relation to the process of progressive autonomy, the idealized notion of the family and the transgressions of gender norms committed by adolescent girls who commit offenses. It is concluded that social and criminal control practices work in the production and reproduction of gender-based on standardized conceptions of adolescent women and their processes of autonomy.